Pengambilan keputusan perceraian pada perempuan Jawa - Devi Puspitasari (INNER: Journal of Psychological Research, 2022)
Abstract This study aims to map the divorce decision-making process for Javanese women from a social, cultural and gender perspective using literature review and survey methods. A survey conducted by the author on 78 Javanese women aged 20-50 years who had filed for divorce from their husbands and had children supported the results of the study. The criteria for Javanese women in this study are born from Javanese ethnicity or descendants of Javanese people from previous generations, have Javanese identity, for example, names that still use Javanese idioms, practice the traditional values ​​of Javanese ancestral culture with their own awareness and willingness and live in a family environment, most of which are still alive. carry out the Javanese tradition. The results of the study show that in traditional Javanese gender roles, women are "guardians" who are responsible for housework, child care, and are obedient to their husbands so that when a divorce occurs, women are often blamed for not being able to maintain the "honour" of their husbands and marital harmony. The survey results show that they consider external factors such as children, family (good name), and social status (widow stigma). The conclusion from the literature review and survey, is that it is not easy for Javanese women to file for divorce, so they often survive in conflict-ridden marriages as long as they are not divorced because Javanese culture upholds the value of marriage. Keywords: divorce decision making, Javanese women, social perspective